2006
DOI: 10.4315/0362-028x-69.7.1565
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Disinfectants To Reduce Listeria monocytogenes on Precut Iceberg Lettuce

Abstract: The efficacy of water, chlorinated water (100 ppm), peracetic acid solution (0.05%), and commercial citric acid-based produce wash (0.25%) to reduce the population of Listeria monocytogenes on precut lettuce was tested. Samples were inoculated with a mixture of equal amounts of five L. monocytogenes strains at a level of 4.7 log CFU/g, and analyzed on the day of washing and after 3 and 6 days of storage at 6 degrees C. Sanitizer reduced the number of L. monocytogenes at maximum 1.7 log CFU/g and number of L. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…Some considerations regarding authorizations for use on produce in the United States are addressed in Table 1. The insights and quantitative estimates generated in this study will be (Akbas & Olmez, 2007;Choi et al, 2012;Hellstrom et al, 2006;Kim, Kim, & Song, 2009a, 2009bLee et al, 2002;Park, et al, 2011;Rodgers et al, 2004;Ruiz-Cruz et al, 2007;Sagong et al, 2011;Szabo et al, 2003;Yuk, Yoo, Yoon, Marshall, & Oh, 2007;Yuk et al, 2006;Zhang & Farber, 1996) Lactic acid is a direct food ingredient affirmed as generally recognized as safe (GRAS) as an antimicrobial agent, and shall meet the identity, limitations, and specifications described in this authorization ( 21 CFR 184.1061).…”
Section: Chlorine Dioxide~0mentioning
confidence: 98%
See 2 more Smart Citations
“…Some considerations regarding authorizations for use on produce in the United States are addressed in Table 1. The insights and quantitative estimates generated in this study will be (Akbas & Olmez, 2007;Choi et al, 2012;Hellstrom et al, 2006;Kim, Kim, & Song, 2009a, 2009bLee et al, 2002;Park, et al, 2011;Rodgers et al, 2004;Ruiz-Cruz et al, 2007;Sagong et al, 2011;Szabo et al, 2003;Yuk, Yoo, Yoon, Marshall, & Oh, 2007;Yuk et al, 2006;Zhang & Farber, 1996) Lactic acid is a direct food ingredient affirmed as generally recognized as safe (GRAS) as an antimicrobial agent, and shall meet the identity, limitations, and specifications described in this authorization ( 21 CFR 184.1061).…”
Section: Chlorine Dioxide~0mentioning
confidence: 98%
“…Some physical control measures including irradiation or pulsed UV light as well as certain biological means of control such as the use of bacteriophages or biocontrol agents have achieved reductions in experimental studies using L. monocytogenes (or other bacteria that may e6 log 10 cfu (Akbas & Olmez, 2007;Baert et al, 2009;Bari, Inatsu, Kawasaki, Nazuka, & Isshiki, 2002;Bari et al, 2003;Beuchat et al, 2004;Beuchat & Brackett, 1990;Beuchat et al, 1998;Burnett et al, 2004;Delaquis, Stewart, Cazaux, & Toivonen, 2002;Deza et al, 2003;Francis & O'Beirne, 2002;Hellstrom et al, 2006;Lang et al, 2004aLang et al, , 2004bLee, Yun, Fellman, & Kang, 2002;Li, Brackett, Chen, & Beuchat, 2002;Rodgers et al, 2004;Ruiz-Cruz et al, 2007;Stopforth et al, 2008;Su & D'Souza, 2012;Szabo, Simons, Coventry, & Cole, 2003;Udompijitkul et al, 2007;Walter et al, 2009;Wei et al, 2005;Zhang & Farber, 1996) Potassium hypochlorite is exempted from the requirement of a tolerance in or on all commodities (40 CFR 180.1300) Calcium hypochlorite is exempt from the requirement of a tolerance when used preharvest or postharvest in solution on all raw agricultural commodities and on grape when used as a fumigant postharvest by means of a chlorine generator pad (40 CFR 180.1054) Sodium hypochlorite is exempted from the requirement of a tolerance for residues and when used in accordance with good agricultural practices as a seed-soak treatment in the growing of the raw agricultural commodities vegetables, brassica, leafy , group 5 and radish, roots and radish, tops (40 CFR 180.1235;40 CFR 180.1070) Not all substances with chlorine are authorized as antimicrobials in the U.S. Calcium hypochlorite is authorized as food contact substance for use as an antimicrobial agent in water used to process fruits, vegetables, nuts, meat, and poultry and in pretreatment of water used in the manufacture of beverages...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in theory at least, the active hypochlorous acid concentration is held constant regardless of the organic loading in the wash water. Peroxyacetic acid is an alternative sanitizer with the advantage over hypochlorite in being relatively stable in the presence of organic material (Beuchat, Adler, & Lang, 2004;Hellstrom, Kervinen, Lyly, Ahvenainen-Rantala, & Korkeala, 2006;Vandekinderen, Devlieghere, De Meulenaer, Ragaert, & Van Camp, 2009;Zhang, Ma, Phelan, & Doyle, 2009). Peroxyacetic acid is recommended to be used at levels in the order of 50 ppm although typically lower concentrations (5e30 ppm) are applied due to cost (Vandekinderen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated the limited ability of chlorine to reduce populations of human pathogens on inoculated lettuce, typically reporting 1-to 2-log reductions, with regrowth during post-treatment storage Zhang and Farber, 1996;Delaquis et al, 2002;Lang et al, 2004;Hellström et al, 2006;Keskinen et al, 2009). Lang et al (2004) reported somewhat greater log reductions with parsley.…”
Section: Efficacy Of Washing and Sanitizing Methods For Problem Commomentioning
confidence: 99%